Poor Banished Children of Eve: Woman as Evil in the Hebrew Bible. By Gale A. Yee. Pp. xii + 298. Minneapolis, MN: Fortress Press, 2003. isbn 0 8006 3457 8. Paper 24 - Dawn, Maggi (The journal of theological studies, 2005)
This book offers a corrective to one of the problematic aspects of feminist hermeneutics: that the attempt to read within the Hebrew Bible a positive and affirming message for women can sometimes lead to a denial of the obvious fact that it not only contains a considerable amount of material oppressive to women, but is, arguably, responsible for much of the oppression of women that has continued throughout Christian history., Yee's alternative approach is to apply a materialist-feminist method to four significant texts—Eve in Genesis, Faithless Israel in Hosea, the two sisters in Ezekiel, and the Other Woman in Proverbs.